ANALISIS MISPERSEPSI MASYARAKAT TERHADAP BANK SYARIAH (STUDI PADA KELURAHAN RAWASARI KECAMATAN ALAM BARAJO KOTA JAMBI) - Dina Meiranda; , Erwin Saputra Siregar (ICONS: Islamic Economics Journal, 2026)
This study aims to analyze public misperceptions toward Islamic banks and the social, cultural, and economic factors influencing them in Rawasari Village, Jambi City. The research employs a qualitative method with a case study and phenomenological approach, using interviews, observations, and documentation, analyzed through data reduction, data presentation, and conclusion drawing validated by triangulation. The results show that most residents still have a low understanding of the concepts and products of Islamic banking, with misperceptions such as assuming that Islamic banks are no different from conventional banks due to administrative fees, and doubts about the halal operations of Islamic banks caused by a lack of transparent information. The main contributing factors include low Islamic financial literacy, social environment influences, cultural stereotypes, and limited access to accurate information. These findings are expected to serve as a reference for Islamic banks, the government, and stakeholders in formulating educational strategies to enhance public understanding and interest in Sharia-based financial services.